Preliminary findings on the effect of childhood trauma on the functional connectivity of the anterior cingulate cortex subregions in major depressive disorder - Rong, Bei; Gao, Guoqing; Sun, Limin; Zhou, Mingzhe; Zhao, Haomian; Huang, Junhua; Wang, Hanling; Xiao, Ling; Wang, Gaohua (Frontiers in Psychiatry, 2023)
Objectives Childhood trauma (CT) is a known risk factor for major depressive disorder (MDD), but the mechanisms linking CT and MDD remain unknown. The purpose of this study was to examine the influence of CT and depression diagnosis on the subregions of the anterior cingulate cortex (ACC) in MDD patients. Methods The functional connectivity (FC) of ACC subregions was evaluated in 60 first-episode, drug-naïve MDD patients (40 with moderate-to-severe and 20 with no or low CT), and 78 healthy controls (HC) (19 with moderate-to-severe and 59 with no or low CT). The correlations between the anomalous FC of ACC subregions and the severity of depressive symptoms and CT were investigated. Results Individuals with moderate-to severe CT exhibited increased FC between the caudal ACC and the middle frontal gyrus (MFG) than individuals with no or low CT, regardless of MDD diagnosis. MDD patients showed lower FC between the dorsal ACC and the superior frontal gyrus (SFG) and MFG. They also showed lower FC between the subgenual/perigenual ACC and the middle temporal gyrus (MTG) and angular gyrus (ANG) than the HCs, regardless of CT severity. The FC between the left caudal ACC and the left MFG mediated the correlation between the Childhood Trauma Questionnaire (CTQ) total score and HAMD-cognitive factor score in MDD patients. Conclusion Functional changes of caudal ACC mediated the correlation between CT and MDD. These findings contribute to our understanding of the neuroimaging mechanisms of CT in MDD.